2022
DOI: 10.1370/afm.2876
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Primary Care: Understanding and Supporting Clinicians’ Use to Enhance Diabetes Care

Abstract: PURPOSEDiabetes affects approximately 34 million Americans and many do not achieve glycemic targets. Continuous glucose monitoring (CGM) is associated with improved health outcomes for patients with diabetes. Most adults with diabetes receive care for their diabetes in primary care practices, where uptake of CGM is unclear.METHODS We used a cross-sectional web-based survey to assess CGM prescribing behaviors and resource needs among primary care clinicians across the United States. We used descriptive statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…A total of 588 (11.8%) respondents completed surveys, with 410 (69.7%) of the respondents completing on paper and 178 (30.3%) online (Table 1 ). These numbers are in line with other survey studies we have completed [ 19 – 23 ]). The majority of the respondents were born in 1970 or later (54.2%), female (52.8%), not Hispanic or Latinx (91.8%), white (74.4%), out of residency for 16 or more years (51.5%), spent 76–99% of their clinical time with adults (54.8%), and worked in an urban setting (84.4%).…”
Section: Resultssupporting
confidence: 91%
“…A total of 588 (11.8%) respondents completed surveys, with 410 (69.7%) of the respondents completing on paper and 178 (30.3%) online (Table 1 ). These numbers are in line with other survey studies we have completed [ 19 – 23 ]). The majority of the respondents were born in 1970 or later (54.2%), female (52.8%), not Hispanic or Latinx (91.8%), white (74.4%), out of residency for 16 or more years (51.5%), spent 76–99% of their clinical time with adults (54.8%), and worked in an urban setting (84.4%).…”
Section: Resultssupporting
confidence: 91%
“…76 Unfortunately, many primary care clinicians are reluctant to use CGM due to their unfamiliarity with the various devices, lack of confidence in interpreting and utilizing the glucose data for therapy decision making, uncertainty about which devices are best suited to specific patients, and the time required to access glucose data. [77][78][79] As reported by Grunberger et al in a recent survey of 100 endocrinologists and 102 primary care clinicians in the U.S., 87.0% of endocrinologists reported using CGM compared with only 28.4% of primary care clinicians. 80 These real world observations provide important directions for new programmatic initiatives that might broaden and enhance the use of this technology in diabetes care.…”
Section: Clinician Reluctance To Utilize Technologymentioning
confidence: 91%
“…Although adoption of CGM in primary care settings has been slow, a recent survey of 656 primary care clinicians found that the majority of respondents (72.3%) indicated that they would be likely to prescribe CGM with if they could receive appropriate education via individual training or workshops. 79 Although clinicians must invest time to learn about the various systems currently marketed, helping them develop expertise in interpreting and utilizing CGM data to optimize insulin titration and non-insulin therapies must be a key component of this training. [82][83][84][85] Modify Electronic Medical Record (EMR) systems.…”
Section: The Futurementioning
confidence: 99%
“…The median (IQR) number of follow-up contacts per participant after completion of the 3 remote training sessions was 8 (6)(7)(8)(9)(10)(11). Follow-up contact formats included video training sessions (74%), telephone calls (13%), emails (8%), and texts (5%).…”
Section: Participants With Type 2 Diabetesmentioning
confidence: 99%
“…Despite primary care clinicians’ interest in CGM use for their patients with diabetes, limited knowledge, technology readiness, and lack of resources are limiting factors in diabetes technology implementation and expansion. 11 Navigating insurance coverage remains a key barrier, as well as access to CGM training support and education to improve understanding of data.…”
Section: Introductionmentioning
confidence: 99%